Misconoscenze di fisica nella scuola del primo ciclo: un questionario didattico - Antonio Calvani; Matteo Leone; Matteo Torre (LED Edizioni Universitarie, 2024)
PHYSICS MISCONCEPTIONS IN FIRST CYCLE SCHOOL: AN EDUCATION QUESTIONNAIRE Abstract The achievement of an adequate level of scientific knowledge is unanimously recognized as an important milestone, not only for training future scientists but above all to enable the new generations to possess important skills for responsible and critically informed citizenship. Regarding Italy, international comparisons highlight the accentuation of specific critical issues in this area. Concerning the search for teaching actions aimed at improving the understanding of physical phenomena, it remains fundamental to understand the preconceptions from which students start and the cognitive obstacles that these entail. We have prepared and validated a questionnaire with the aim of highlighting the most common critical elements in the explanation of physical phenomena by students aged 11-14. The collected data confirm the presence of widespread misconceptions already reported in the literature, which it is appropriate to bring to the attention of teachers. The questionnaire is complemented by formative feedback intended to provide initial indications for their revision.